The potential of soil surface arthropods in spinach plantation. Issue 1 (October 2020) - Aminah, S N; Abdullah, T; Gassa, A; Fatahuddin,; Miranda, R
Abstract: The purpose of the research is to study the role of soil surface arthropods in spinach plantation. The experimental research was held in Moncobalang village, Gowa district, South Sulawesi, Indonesia. The findings of the research were showed the highest order is: Coleoptera (Coccinellidae) (-0.35) similar to Diptera (Tachinidae), Hymenoptera (Vespidae) (-0.28). Arachnida as a potential predator such as Lycosidae and Pholcidae (-0.20) and (-0.15), respectively. The total number from collected arthropods in a yellow trap about 131 individuals. In the future, the result of research is very useful information for management potential soil surface arthropods in improving the quality of spinach harvest and monitoring the presence of insect pest based environmentally friendly methods.